2004
DOI: 10.1111/j.0300-9475.2004.01389.x
|View full text |Cite
|
Sign up to set email alerts
|

Serum‐Soluble Selectin Levels in Patients with Rheumatoid Arthritis and Systemic Sclerosis

Abstract: Soluble forms of selectins may play a regulatory role in inflammatory responses that are key to the pathophysiology of rheumatic diseases such as rheumatoid arthritis

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
31
1
3

Year Published

2007
2007
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 32 publications
7
31
1
3
Order By: Relevance
“…Moreover, higher levels of sE-selectin in patients with SSc compared with healthy controls were observed, consistent with the results from other studies [14,20]. Despite endothelial origin of both sE-selectin and NT-proCNP and their role in inflammatory process, we failed to detect the significant correlation between the molecules.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Moreover, higher levels of sE-selectin in patients with SSc compared with healthy controls were observed, consistent with the results from other studies [14,20]. Despite endothelial origin of both sE-selectin and NT-proCNP and their role in inflammatory process, we failed to detect the significant correlation between the molecules.…”
Section: Discussionsupporting
confidence: 90%
“…Ates et al [14] reported that serum sP-selectin concentrations were similar in patients with SSc and controls, but sE-selectin levels were found to be increased in the SSc group. Regarding sP-selectin, the discrepancy between our results and those by Ates et al may come from different patient profiles in both studies.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…This interaction is in part modulated by ET-1, which, through inhibition of P-selectin upregulation, prevents interactions between leukocytes and endothelium, particularly in the presence of vasoconstriction and inflammation 30 . As P-selectin levels in patients with SSc may also be related to extensive systemic inflammation 31,32 , it is possible that the antagonist effect of bosentan on ET-1 receptor disrupts the compensatory mechanism, eventually leading to sP-S upregulation. This complex interaction may eventually translate into treatment failure.…”
Section: Rheumatologymentioning
confidence: 99%
“…The role of P-selectin expression may vary widely, depending on the presence of articular and extra-articular rheumatoid manifestations. This is why in some observations soluble P-selectin levels were close to normal [71] or there were no associations with shifts of immune markers (e.g., soluble IL-2 receptor, a modulating protein of T-lymphocyte activity) [61].…”
Section: Soluble P-selectinmentioning
confidence: 98%